2020
DOI: 10.3389/fmars.2020.00225
|View full text |Cite
|
Sign up to set email alerts
|

General DNA Methylation Patterns and Environmentally-Induced Differential Methylation in the Eastern Oyster (Crassostrea virginica)

Abstract: Epigenetic modification, specifically DNA methylation, is one possible mechanism for intergenerational plasticity. Before inheritance of methylation patterns can be characterized, we need a better understanding of how environmental change modifies the parental epigenome. To examine the influence of experimental ocean acidification on eastern oyster (Crassostrea virginica) gonad tissue, oysters were cultured in the laboratory under control (491 ± 49 µatm) or high (2550 ± 211 µatm) pCO 2 conditions for 4 weeks. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 74 publications
8
38
0
Order By: Relevance
“…The number of hypermethylated genes were higher than hypomethylated genes under OA (Figure S6ii in File S1) which is similar to the observations in an oyster Crassostrea virginica and coral ( Pocillopora damicorni s) species under OA (Putnam et al, 2016; Venkataraman et al, 2020). However, global DNA methylation levels do not always increase under stressors as hypomethylation also occurs in response to stressors (Bogan et al, 2020; Gonzalez‐Romero et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…The number of hypermethylated genes were higher than hypomethylated genes under OA (Figure S6ii in File S1) which is similar to the observations in an oyster Crassostrea virginica and coral ( Pocillopora damicorni s) species under OA (Putnam et al, 2016; Venkataraman et al, 2020). However, global DNA methylation levels do not always increase under stressors as hypomethylation also occurs in response to stressors (Bogan et al, 2020; Gonzalez‐Romero et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…Crassostrea virginica exhibited a subtle genome-wide DNA methylation response to high OA, similar to the gene expression response of C. virginica . This genome-wide DNA methylation response to OA has been found in several other species of marine calcifiers, including corals, pteropods, and in the gonadal tissue of C. virginica (Putnam et al, 2016;Liew et al, 2018;Bogan et al, 2020;Venkataraman et al, 2020) . In the present study, OA was associated with a genome-wide decrease in methylation (hypomethylation), similar to the response observed in pteropods (Bogan et al, 2020) , but opposite the response observed in corals (Putnam et al, 2016;Liew et al, 2018) .…”
Section: Dna Methylationmentioning
confidence: 65%
“…Interestingly, the overall response of individual loci to OA was quite small (85 DML across both time points) in the mantle tissue compared to the gonadal tissue (Venkataraman et al, 2020) , which exhibited hundreds of differentially methylated loci. Although the differential results amongst tissue types may arise from differences in methodologies, the distinct lack of overlap in DML suggests that a fundamental difference in responses exists amongst different tissue types.…”
Section: Dna Methylationmentioning
confidence: 99%
See 2 more Smart Citations